The celebration of authenticity in Howl’s moving castle - Tan, Cheryl Si Ying (2015)
Howl’s Moving Castle is the first in a trilogy of children fantasy novels by British novelist Diana Wynne Jones (1934-2011). Sophie Hatter, the protagonist of the story, is a young girl leading a mundane and reclusive life as a hatter. However, when the Witch of the Waste puts a curse on her and turns her into an old woman, Sophie embarks on a journey to free herself from the curse with the assistance of a wizard, Howl, and his fire demon Calcifer. Published in 1986, Howl’s Moving Castle was adapted by renowned film producer and director, Hayao Miyazaki, into a Japanese animated film in 2004. Prior to the release of the Miyazaki adaptation, Jones was known for her Chrestomanci series and Howl’s Moving Castle was comparatively less well-known . The well-received animation was nominated for the Academy Award’s Best Animated Feature, and gave the novel more public attention. Despite the achievements of the adaptation, many scholars and critics continue to neglect Howl’s Moving Castle in favor of her other fiction. The limited scholarly research on Howl’s Moving Castle are focused on comparing the novel with the film adaptation and in light of this, this dissertation will concentrate on the novel itself and argue that it celebrates authenticity through its presentation of the physical body, narrative spaces, and narrative structure.